SPESIALISASI DAN SEKTOR POTENSIAL DI KABUPATEN ACEH BESAR TAHUN 2011-2015 - Zakaria Zakaria (JURNAL EKOMBIS, 2018)
The main aims of this observation are to examine specialized and the issues of base sector for the economy in Aceh Besar during period 2010-2015. The analysis methods applied in this study are Shift Share Analysis, Shift Share Modification Esteban Marquillas and Location Quotient. The Results of the study analysis known that were transformation of economic structure from primary sector to secondary sector in Aceh Besar. While the contribution of of secondary sector, primary sector and then tersier sector which had contributed to PDRB in Aceh besar continually. The base sector which is based on shift share analysis and location quotient analysis are including retail trading sector; repair of motor, transportation and storage sector. Agriculture, forestry and fishing sectors are not include to this sector which has comparative advantages, even though the contribution of economic structure of Aceh Besar is still dominated of those sectors. It shows such sectors are not really being a priority issue to be a main agricultural central for the district government.The district government of Aceh Besar is expected to be more notice and promote the sector tertier such as retail trading sector; repair of motor, transportation and dtorage sector. Agriculture, forestry and fishing, and also accommodation and infrastructures. For those who have the authority is also expected to be more notice and develop economic sectors which are belonging to Aceh. This issues can be solved through potentiality policy for extend economic sector.                   Keywords: Structural Economic, Spesialized Sector, Base Sector